The impact of climate change on U. K. river flows: A preliminary comparison of two generations of probabilistic climate projections. Issue 4 (26th November 2019) - Kay, Alison Lindsey; Watts, Glenn; Wells, Steven C.; Allen, Stuart
Abstract: The impacts of climate change on future river flows are a growing concern. Typically, impacts are simulated by driving hydrological models with climate model ensemble data. The U.K. Climate Projections 2009 (UKCP09) provided probabilistic projections, enabling a risk‐based approach to decision‐making under climate change. Recently, an update was released—UKCP18—so there is a need for information on how impacts may differ. The probabilistic projections from UKCP18 and UKCP09 are here applied using the change factor method with catchment‐based hydrological modelling for 10 catchments across England. Projections of changes in median, mean, high, and low flows are made for the 2050s, using the A1B emissions scenario from UKCP09 and UKCP18 as well as the RCP4.5 and RCP8.5 emissions scenarios from UCKP18. The results show that, in all catchments for all flow measures, the central estimate of change under UKCP18 is similar to that from UKCP09 (A1B emissions). However, the probabilistic uncertainty ranges from UKCP18 are, in all cases, greater than from UKCP09, despite UKCP18 having a smaller ensemble size than UKCP09. Although there are differences between the central estimates of change using UKCP18 RCP4.5, RCP8.5 and A1B emissions, there is considerable overlap in the uncertainty ranges. The results suggest that existing assessments of hydrological impacts remain relevant, though it will be necessary to evaluate sensitive decisions using the latest projections. The analysis will aid development of advice to users of current guidance based on UKCP09 and help make decisions about the prioritization of further hydrological impacts work using UKCP18, which should also apply other products from UKCP18 like the 12‐km regional data.